On the crashworthiness of steel-plated structures in an arctic environment: An experimental and numerical study - Park, D.K. (American Society of Mechanical Engineers (ASME), 2015)
Structural crashworthiness with regard to crushing and fracture is a key element in the strength performance assessment of ship collisions in the Arctic. The aim of this study is to investigate the crashworthiness characteristics of steel-plated structures subject to low temperatures that are equivalent to the Arctic environment. The effect of low temperatures on the material properties is examined on the basis of tensile tests. Crushing tests are undertaken on steel-square tubes subject to a quasi-static crushing load at both room and low temperatures. The crushing behavior of the square tubes in this test is compared with LS-DYNA computations. It is found that low temperatures have a significant effect on not only the material properties but also the crashworthiness of steel-plated structures in terms of mean crushing loads and brittle fracture. It is suggested that the collisionaccidental limit state design of ships intended to operate in the Arctic region should be carried out by taking the effect of low temperatures into account. Â© 2015 by ASME.